RANCANGAN TUNGKU PEMANAS UNTUK PROSES PENGERASAN KOMPOSIT DENGAN METODE WET LAY UP DI PROGRAM STUDI TEKNIK PESAWAT UDARA SEKOLAH TINGGI PENERBANGAN INDONESIA - Muhammad Riezky Utama; Ego Widoro; Djoko Herwanto (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The final objective of this design is to optimize the curing process in the manufacture and repair of composite panel for interchanges curing process using a heat gun, because by using a heat gun the curing process is not optimal. The design focuses on making the furnace only on the other parts are designed on other designs. The goal that must be achieved is to make optimal heat distribution in the furnace. Tests carried out to get all the components that did not change the shape during the composite curing process that occurred, components that did not change from the shape received, and the length of expansion of the work-piece within the specified range. Will there be one criterion which has not yet been agreed upon, the top surface of the furnace wall is 41.7 ℃ causes the surface of the upper wall to pass through a predetermined range affecting the buoyancy force which causes the air density to decrease and hot air as it moves upward. This is what causes heat transfer to the surface which is higher than the other sides